2021
DOI: 10.1002/tcr.202000156
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Functional Luminescence Properties Based on Flexible and Bendable Boron‐Fused Azomethine/Azobenzene Complexes with O,N,O‐Type Tridentate Ligands

Abstract: Azomethine (C=N) and azo (N=N) scaffolds are a part of structural units in poly(p‐phenylene azomethine) (PAM) and poly(p‐phenylene azo) (PAZ), respectively. Poly(p‐phenylene vinylene) (PPV) is known to be one of luminescent π‐conjugated polymers, meanwhile PAM and PAZ, which are the aza‐substituted PPV analogues, are regarded as weak or no emissive materials. However, by the boron complexation, intense emission can be induced. Furthermore, environment‐sensitivity and stimuli‐responsivity were also observed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 115 publications
0
17
0
Order By: Relevance
“…We recently reported the series of solid-state luminescent complexes and polymers containing boron-fused azomethine (À C=NÀ ) [35][36][37][38][39] and azo (À N=NÀ ) [40][41][42][43][44] complexes with the tridentate ligands, o-salicylideneaminophenol or 2,2'-dihydroxyazobenzne scaffold, respectively. [45] These materials showed intense emission in the condensed state, and highlyefficient polymer film emission [38] and near-infrared (NIR) absorptive and emissive characteristics [40][41][42]44] were obtained. It should be emphasized that unique environment-sensitive luminescent properties, such as aggregation-induced emission (AIE), [46,47] crystallization-induced emission enhancement (CIEE), [48] in which enhanced emission can be observed only in aggregation and crystal, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the series of solid-state luminescent complexes and polymers containing boron-fused azomethine (À C=NÀ ) [35][36][37][38][39] and azo (À N=NÀ ) [40][41][42][43][44] complexes with the tridentate ligands, o-salicylideneaminophenol or 2,2'-dihydroxyazobenzne scaffold, respectively. [45] These materials showed intense emission in the condensed state, and highlyefficient polymer film emission [38] and near-infrared (NIR) absorptive and emissive characteristics [40][41][42]44] were obtained. It should be emphasized that unique environment-sensitive luminescent properties, such as aggregation-induced emission (AIE), [46,47] crystallization-induced emission enhancement (CIEE), [48] in which enhanced emission can be observed only in aggregation and crystal, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] Based on this concept, we have developed main-chain-type p-conjugated molecules and polymers with boron-fused azo (NQN) or azomethine (CQN) groups. 25,[50][51][52][53][54][55][56][57] They showed various functions such as film-state visible to NIR emission, 25,[51][52][53][54]57 stimuliresponsiveness, 25 aggregation-induced emission (AIE), 53,54,57,58 and crystallized-induced emission enhancement (CIEE). 51,52,[59][60][61][62][63] Hypervalent compounds are a class of molecules in which over eight electrons are formally assigned around a valence shell of a main group element beyond the limit of the Lewis octet rule.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, high co-planarity enhances the overlap of aromatic π-orbitals and increases the effective conjugation length. However, interestingly, our results indicate that the waving and flexible units by BAz derivatives (dihedral angle of azobenzene ≈ 165°) [41,45] might be suitable for expansion of effective conjugation length in comparison to the rigid and planar units by TAz derivatives (dihedral angle of azobenzene ≈ 180°) [64] (Figure S2).…”
Section: Optical Measurementsmentioning
confidence: 86%
“…By using this concept, various types of heteroatom-containing π-conjugated building blocks have been developed [36][37][38][39][40]. More recently, we have reported that boron-fused azobenzene/azomethine (BAz/BAm) complexes, which are "boron element-blocks", worked as unique functional building blocks [41][42][43][44][45][46][47][48][49][50][51]. For example, by using strong electron-accepting ability of BAz and BAm complexes, the π-conjugated polymers with highly efficient emission from visible to NIR region both in solution and film states were able to be prepared by construction of donor-acceptor (D-A) systems [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%